Presence and localisation of calbindin-D28k in the kidney and cerebellum of the red squirrel (Sciurus vulgaris) - Aydin, A; Karan, M; Timurkaan, S (Ecole Nationale Veterinaire Toulouse, 2005)
Distribution of the calcium binding protein, calbindin-D28k, an intracellular protein with a high affinity for calcium, was examined in the kidney and cerebellum of Sciurus vulgaris using immunohistochemical techniques. This protein is exclusively localised in the distal convoluted tubules of the kidney and in Purkinje cells of the cerebellum. This distribution was similar to findings in avian, reptilian and mammal species. Functionally, calbindin-D28k is supposed to be involved in the regulation of the reabsorption of calcium in the distal nephron, and in the control of free Ca2+ concentrations in neurones, although the exact regulatory mechanisms are not yet known.
Keywords: calbindin; calcium; kidney; cerebellum; Sciurus vulgaris; immunohistochemistry